Pendampingan Penguatan Literasi dan Numerasi Guru dalam Menghadapi Kurikulum Merdeka - Mutia Fonna; Ratna Unaida; Siraj Siraj; Halimatus Sakdiah; Ika Aulia Putri; Aura Fitria Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
The change of the curriculum to the Independent Curriculum made the National Exam (UN) officially change to the Minimum Competency Assessment (AKM). The evaluation carried out in the National Assessment consisted of reasoning ability using language (literacy), reasoning ability using mathematics (numeracy), and strengthening character education. Despite the lack of significant improvement in Indonesia's literacy, numeracy, and science skills rankings over the past 18 years, the country consistently ranks in the bottom 10 in PISA test results. Facing the current Independent curriculum, teachers must be able to teach based on literacy and numeracy skills, because this is the indicator in AKM and PISA-based assessments. If teachers master literacy and numeracy skills, then teachers can convey materials related to literacy and numeracy clearly and correctly for students. Teachers are expected to innovate to develop student competencies through various lessons through student-centred teaching. This Community Service is a community partnership program in collaboration with SMKN 3 Lhokseumawe. Service activities are by providing material on literacy and numeracy-based learning. During the service program, teachers are given knowledge about literacy and numeracy, the form of questions, and the number of percentages of questions in the AKM, which are useful for strengthening teachers' literacy and numeracy.